Education Students’ Knowledge and Perceptions of Collaborative Learning and Implications for Future Use in Their Field - Grunzke, Peyton; Dunbar, Laura (My University, 2019)
Collaborative learning (CL) - a situation where two or more people learn or attempt to learn together - has become common in United States classrooms. It is known that students’ perceptions of their learning context influence consequential learning outcomes, however, little research has been done on student perspectives of CL, especially in a teacher education context. The purpose of this study is to investigate what education students know about CL, how knowledge on the theoretical concepts regarding CL affects learning outcomes, and how this experience with CL in combination with a collaborative project will influence participants' use of CL. We studied a collaborative project as a part of a fine arts integration course for Middle Childhood to Early Adolescence (MCEA) education majors using pre- and post- surveys and professor interviews. The content was qualitatively analyzed for recurring themes. Results suggest students recognize CL as a concept; however, preservice teachers have a very shallow understanding of the elements necessary to constitute CL, which could potentially limit the benefits they receive from CL. We conclude that further research is needed investigating education students’ perspectives and understandings of CL, and how their understanding of CL affects their future use of CL.
Color poster with text and images.
Keywords: Team learning approach in education; Teacher education; Posters